A Study of African and Western Epistemic Intuitions and Implications for Decolonisation - Lembethe, Nolwandle Ayanda (University of the Witwatersrand, Johannesburg, 2024)
Discussions surrounding decolonisation in academic spaces in South Africa took a turn in 2015 when student protests forced the academy or academic landscape to revisit its relationship with Eurocentrism. This had far reaching consequences, as institutions of higher learning began to interrogate different aspects of academic culture including knowledge production. My thesis looks at decolonisation from an epistemic lens by principally interrogating the use of epistemic intuitions and their relevance to the decolonisation project. By examining experimental philosophy as a methodology, my research provides some meaningful ways in which we can broaden our understanding and use of epistemic intuitions. I draw on different ways scholars in feminist theory have extrapolated methods from lived experiences and epistemic standpoints of epistemically marginalised groups to point out the marginalizing nature of experimental philosophy. The contribution that my thesis makes to knowledge then is that it helps to show how and why experimental philosophy should be made more inclusive to worldviews that have been otherwise marginalised by dominant research methods.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Epistemology; experimental philosophy; decolonisation; epistemic intuition; SDG-17: Partnerships for the goals